2014
DOI: 10.1007/s10909-014-1226-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Counterflow in a Periodic Channel with Solid Boundaries

Abstract: We perform numerical simulations of finite temperature quantum turbulence produced through thermal counterflow in superfluid 4 He, using the vortex filament model. We investigate the effects of solid boundaries along one of the Cartesian directions, assuming a laminar normal fluid with a Poiseuille velocity profile, whilst varying the temperature and the normal fluid velocity. We analyze the distribution of the quantized vortices, reconnection rates and quantized-vorticity production as a function of the wall-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 40 publications
8
34
1
Order By: Relevance
“…3a,c. The VLD is higher near the walls, similar to the steady-state tangles with the parabolic profile of the driving normal-fluid velocity, obtained under periodic streamwise conditions [25][26][27]29,36 . Two edges of the tangle are different: a narrow and sharp edge is formed in the direction of V n and a wide and less steep edge in the direction of V s .…”
Section: Evolution Of Vldsupporting
confidence: 77%
See 1 more Smart Citation
“…3a,c. The VLD is higher near the walls, similar to the steady-state tangles with the parabolic profile of the driving normal-fluid velocity, obtained under periodic streamwise conditions [25][26][27]29,36 . Two edges of the tangle are different: a narrow and sharp edge is formed in the direction of V n and a wide and less steep edge in the direction of V s .…”
Section: Evolution Of Vldsupporting
confidence: 77%
“…Recent advances in the experimental techniques, including flow visualization [22][23][24] , as well as increasing computing power, renewed the interest to the spatial inhomogeneity due to presence of channel walls 19,[25][26][27][28][29][30][31] and spatially-resolved investigations of the transient behavior in the thermal counterflow 32 . The latter work showed that the vortex tangle that eventually fills the whole channel, grows starting from a number of remnant vortex rings.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex tangle reaches the statistically steady state even if the counterflow is spatially inhomogeneous. The fluctuations are much larger than those in uniform counterflow [31] or those between two parallel plates [74,75]. The period of the oscillation is about 0.7 s, and the oscillation consists of four stages (a)-(d).…”
Section: Poiseuille and Tail-flattened Normal Flow In A Ductmentioning
confidence: 95%
“…Therefore, it does not require any empirical assumption on the flow. Let us mention that such requirement is more difficult to fulfill [55] in vortex line (or vortex point) simulations of counterflows [18,[56][57][58][59][60][61][62]. Finally, the HVBK model has already served as a mathematical basis for a number of previous numerical counterflow studies, e.g., see Refs.…”
Section: B the Governing Equations Under A Boussinesq-like Hypothesismentioning
confidence: 99%